Effects of Dietary Antioxidant on Performance and Physiological Responses Following Heat Stress in Laying Hens - Felver-Gant, J.N.; Dennis, R.L.; Zhao, J.; Cheng , H.W. (International Journal of Poultry Science, 2014)
Heat stress (HS) causes oxidative damage, increasing mortality and reducing productivity in chickens. The objective of this study was to determine the benefits of antioxidant supplementation in laying hens during HS. Eighty 32-week-old W-36 White Leghorn hens were used in this study. Hens were randomly pair-housed in two adjacent rooms and fed a control diet (CF) or control diet mixed with Agrado Plus Ultra®, an antioxidant, at 160 mg/kg (AF) for two weeks. One room was then subjected to a hot climate (H) (33°C) for 8 days. Physical and physiological data were collected at day 1 and 8 during the treatment. Core body temperature was increased (p